The Legal Implications of the Right to Retention: A Comparative Study of Creditor Protection in Civil Law Systems - kedjar , Zahia Houria (Journal of Science and Knowledge Horizons, 2025)
This paper aims at explaining the concept of the right to retention as a legal device for the protection of creditors, as a tool for safeguarding creditors and ensuring payment security. Highlighted are its benefits in protecting creditor rights by comparing its utilization in frameworks such as the Algerian, French and Egyptian Civil Codes. The study explores the prerequisites for invoking this right. How it proves advantageous. Case studies, from sales, easements and deposits demonstrate applications of the right to retention to ensure payment and asset protection. The paper also discusses how the right to retention stacks up, against ways creditors protect themselves like mortgages and pledges by pointing out its simplicity and direct use but also mentioning its limitations well. Ultimately though when you compare these methods you see that while the right to retention has its perks it works best in situations where ownership of property is crucial, to the creditors case.